Экстремальные итерационные методы в обратной задаче магнитометрии при косом намагничении - Миненко, П.А. (Видавничий дім "Академперіодика" НАН України, 2007)
Practical examples of the use of iterative methods of solving the inverse linear and nonlinear problems of magnetic measurements with the application of extreme algorithms to the calculation of depths up to the horizontal borders of the section of blocks and three components of the magnetism intensity vector of rocks are given. The results will be useful in the detailed geological mapping and the search for ore deposits.